An AHP-Based Decision Support System for Selecting the Best Service Between GrabBike Hemat and GrabBike Standard - Afifah Trista Ayunda; Hendra Mayatopani; Ahmad Abdillah Hisyam (Indonesian Applied Research Computing and Informatics, 2025)
The development of online ride-hailing transportation services in Indonesia has introduced various service options, such as GrabBike Economy and GrabBike Standard, each offering distinct advantages in terms of cost, travel time, comfort, and safety. This study aims to develop a Decision Support System (DSS) based on the Analytic Hierarchy Process (AHP) method to assist Grab users in selecting the service that best matches their preferences. A quantitative research approach was employed, with data collected through an AHP pairwise comparison questionnaire distributed to 31 Grab users in the Tangerang area. The analysis revealed that cost was the most influential criterion, with a weight of 60.0%, followed by travel time (24.9%), comfort (10.4%), and safety (4.6%). Overall, GrabBike Economy achieved a higher aggregate priority score of 52.6%, slightly outperforming GrabBike Standard at 47.4%. These findings indicate that users prioritize affordability over comfort and safety when choosing ride-hailing services. However, the Consistency Ratio (CR) of 27.5% suggests that respondents' judgments were not sufficiently consistent. This study concludes that the AHP method is effective in supporting multi-criteria decision-making within the context of online ride-hailing transportation and provides practical insights for service providers to develop strategies that better align with user preferences.